Vulnerabilidade dos profissionais de enfermagem em um hospital público frente ao risco ocupacional no manuseio de quimioterápicos antineoplásicos - Paula, Nayara de Almeida (2022)
The exposure vulnerability of the nursing team that works in the process of administration and disposal of chemotherapy waste, exposes these professionals to a high risk of physical health problems. This observation aroused the concern to investigate and synthesize the knowledge already produced, seeking the best evidence for the improvement of professional practice. Therefore, the present work aims to evaluate and synthesize results of studies published from 2010 to the present moment, which investigated the occupational risks resulting from the handling of chemotherapy drugs by nursing professionals, and also aims to understand the reality experienced by the nursing team of the institution evaluated, who work in sectors where there are chemotherapy procedures, highlighting the vulnerabilities that professionals are exposed to in the work environment. The proposed methodologies were: integrative literature review; publications from the Virtual Health Library (VHL) and from the PUBMED, Scielo and Lilacs platforms were used, and an observational, cross-sectional, descriptive research, with a mixed, quantitative and qualitative methodological approach, with the application of a questionnaire to fourteen professionals from the health care team. nursing in the oncology sector of a Public Hospital in Minas Gerais. After applying the inclusion and exclusion criteria, 21 articles were selected for the final composition of the sample. The results of the studies included in this review pointed to the following problems resulting from exposure to antineoplastic drugs: genetic damage, impaired fertility in women, appearance of oral ulcers, leukocyte count below average, creatinine rate above average. The main causes of occupational exposure found in the articles addressed at work are: (23.81%) ineffective cleaning and sanitation; (19.05%) little knowledge, lack of training, accidents with the preparation or administration of anticancer drugs, inadequate use of personal protective equipment (PPE). (9.52%) inadequate prevention and safety controls; (9.42%) inefficient communication and problems with intravenous tube administration; (4.76%) contaminated clothing without disposal or hygiene and absence of annual medical check-ups. The applied research highlighted the importance of improving the institution's operational management system, as it was reported that there is an insufficient number of employees in the oncology sector. It is also necessary for the institution to offer periodic maintenance of the equipment, as many of them are necessary to minimize the risks of exposure. The institutional incentive for the continuous training process, and for prior training of workers who work in the handling and administration of anticancer drugs, is insufficient, as 50% of the participants are unaware of the protocol and the flow of post-exposure care to antineoplastic chemotherapy, and also do not received information about biosafety standards and risks before starting work with chemotherapy. It is important that the institution establish a manual of conduct that determines the basic guidelines for the implementation of measures to protect the safety and health of health service workers.